Effect of partial replacement of sucrose with sorbitol on the quality characteristics of traditional Malaysian sponge cake (Bahulu) - Mustapha, Nor Afizah; Mahmud @ Ab Rashid, Nor Khaizura; Zainal Abedin, Nur Hanani; Wan Ibadullah, Wan Zunairah; Mohamad Nayan, Nurain Wahida (Hibiscus Publisher, 2024)
Bahulu, the traditional Malaysian sponge cake, is one of the most popular local desserts. During extended storage, the cake typically experiences undesirable physical changes such as dry and crumbly texture. Polyols are widely used in bakery products due to their effectiveness as humectants while reducing overall calorie content. This study investigated the effects of partial replacement of sucrose with different levels of sorbitol; 4, 8, 12 % (w/w) on the bahulu batter and the final product's properties. The batter's specific gravity decreased with sorbitol, implying a better retention of air cells during the whipping process.cIn contrast, the viscosity of the batter decreased with the addition of sorbitol. The weight loss and water activity decreased, while the moisture content increased with sorbitol level, which is due to the higher ability of the polyol to bind water, resulting in a moister cake with a higher bound water content. The cake volume decreased, while the density increased with increasing sorbitol concentration. The polyol resulted in bahulu with a lighter crust color. The partially replaced sugar with sorbitol resulted in bahulu with a less crumbly texture and improved microbial stability.